The basic helix–loop–helix transcription factor BETA2/NeuroD is expressed in mammalian enteroendocrine cells and activates secretin gene expression - Mutoh, Hiroyuki (The National Academy of Sciences of the USA, 1997)
The gene encoding the hormone secretin is expressed only in enteroendocrine S cells and insulin-producing pancreatic β cells during development. A 120-bp enhancer directs cell-specific expression of the rat secretin gene in secretin-expressing cells. The enhancer includes an E-box sequence, CAGCTG, which is important for transcriptional activity. To further characterize the role of the E box, a consensus binding site for basic helix–loop–helix (bHLH) proteins, we have examined factors that interact with this element in the secretin gene. The results suggest that transcription is activated by a recently isolated tissue-specific bHLH protein, BETA2, heterodimerized to the ubiquitously expressed bHLH proteins, Pan 1 and Pan 2, the rodent homologues of E47 and E12. The importance of BETA2 for transcriptional activation of secretin is further illustrated by antisense experiments inhibiting BETA2 expression in secretin-producing cell lines, which resulted in the inhibition of most E box-dependent transcription. Expression of BETA2 in a nonendocrine cell line conferred the ability to express secretin-reporter genes that are transcribed at minimal levels in the absence of BETA2. Secretin-producing enteroendocrine cells in the murine small intestine showed specific immunostaining with BETA2 antibodies, corroborating observations in cell lines. Thus BETA2 is to our knowledge the first transcription factor identified that specifically activates cell type-specific expression of an intestinal hormone gene.